2018
DOI: 10.1002/2017jb014633
|View full text |Cite
|
Sign up to set email alerts
|

Shear Modulus Dispersion in Cracked and Fluid‐Saturated Quartzites: Experimental Observations and Modeling

Abstract: The effect of pore fluids on acoustic wave dispersion in rocks with low aspect ratio crack porosity is important for the interpretation of laboratory and field observations in hard rock mineral exploration environments. Here we make laboratory measurements of shear modulus dispersion at frequencies 0.01–1 Hz and at 1 MHz with different saturating fluids (dry, argon, and water saturated) in two thermally cracked quartzite samples with ~2% total porosity. Measurements are made across a range of effective pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…These experiments have revealed that as a sample is subjected to increasing differential stress, compressional wave velocity ( V P ) and shear wave velocity ( V S ) first increase due to the closure of preexisting cracks, mainly oriented normal to the direction of compression, and then decrease as cracks form and propagate at higher differential stresses that approach rock failure. These changes in elastic wave velocities agree well with theoretical considerations, in which elastic properties are related to the geometry and density of cracks distributed throughout a specimen (e.g., Cheng & Toksöz, ; Guéguen & Schubnel, ; Kachanov, ; O'Connell & Budiansky, ; Schijns et al, ; Walsh, ).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…These experiments have revealed that as a sample is subjected to increasing differential stress, compressional wave velocity ( V P ) and shear wave velocity ( V S ) first increase due to the closure of preexisting cracks, mainly oriented normal to the direction of compression, and then decrease as cracks form and propagate at higher differential stresses that approach rock failure. These changes in elastic wave velocities agree well with theoretical considerations, in which elastic properties are related to the geometry and density of cracks distributed throughout a specimen (e.g., Cheng & Toksöz, ; Guéguen & Schubnel, ; Kachanov, ; O'Connell & Budiansky, ; Schijns et al, ; Walsh, ).…”
Section: Introductionsupporting
confidence: 85%
“…This finding is consistent with the results of previous dry experiments on the deformation of granite (Lockner et al, ) and sandstone (Ayling et al, ; Wulff et al, ). However, because of large differences in frequencies between laboratory experiments and seismic observations (e.g., Murphy, ; Pimienta et al, ), caution is needed before laboratory results can be used to make inferences about these geological problems, particularly in the case of fluid‐bearing cracks that likely contain a frequency‐dependent component (e.g., Li et al, ; Schijns et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar pressure dependencies of the extent of bulk modulus dispersion between seismic and ultrasonic frequencies have been reported for Icelandic basalt (Adelinet et al, ; Fortin et al, ) and for Fontainebleau sandstones (Fortin et al, ; Pimienta et al, , ). Dispersion of elastic moduli and/or frequency‐dependent attenuation have also been observed in other forced oscillation studies of various rock types: sandstones (Mikhaltsevitch et al, ), carbonates (Adam & Batzle, ; Adam et al, , ; Batzle et al, ), shales (Delle Piane et al, ), and quartzites (Schijns et al, ).…”
Section: Discussionmentioning
confidence: 52%
“…In the following, we will present a series of modulus measurements conducted over a broad frequency band, by the collaborating research institutions (see also Schijns et al, ). For the first time, forced oscillation, resonant bar, and ultrasonic wave propagation methods are combined in a broadband study of synthetic soda‐lime‐silica glass samples of controlled microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…They observed Young's modulus dispersion between 0.01 Hz and 500 MHz in water‐saturated conditions with a maximum of ~26% for S waves and ~9% for P waves at the lowest effective pressure tested (1 MPa), and the highest crack density (~0.5). Schijns et al () tested the seismic properties of dry and fluid‐saturated thermally cracked quartzite with ~2% total porosity between 10 and 150 MPa effective pressures. Ultrasonic and low frequency torsional forced oscillation measurements reveal that the shear modulus increases by more than 70% for the two specimens from 1 to 1 MHz, for water saturation at 20 MPa differential pressure.…”
Section: Introductionmentioning
confidence: 99%